Optimization of E-Litigation in the Settlement of Divorce Cases at the Bangkinang District Court - Hanifah, Mardalena; Pascadinianti, Meidana; Triyananda, Maulidya; Firmanda, Hengki; Lestari, Rika; Putra, Setia (Universitas Negeri Semarang, 2024)
The presence of E-Litigation, a Supreme Court innovation to merge procedural law with technology, reflects Indonesian judicial administration in the digitalization era. The existence of E-Litigation as a practical application of the principle of simplicity, speed, and cheap cost is not yet optimal. The Supreme Court Regulation Number 1 of 2019 on Electronic Court Case Administration regulates e-litigation proceedings. Improvements have been made to the legislation. Based on the foregoing, it is judged necessary and urgent to investigate optimizing e-litigation in the settlement of divorce cases at the Bangkinang District Court. The study sought to explain the effectiveness of e-litigation in resolving divorce cases at the Bangkinang District Court. Sociological legal research is an empirical study that seeks to uncover theories about the incidence of law in society. The data was gathered through interviews with judges Syofia Nisra, Ersin, and Aulia Fhatma Whidhola. Not only are the rules for e-litigation processes being reviewed, but so are the hurdles to e-litigation settlement of divorce cases at the Bangkinang District Court. This study is likely to make a significant contribution to legal innovation in the subject of civil procedure law. The settlement of divorce cases through e-litigation will alter the practice of litigating in court. The notion of complicating divorce is analogous to an emergency door on an airplane that should not be utilized unless necessary to overcome a problem. E-litigation processes at the Bangkinang Court have not gone smoothly because the parties do not comprehend and lack suitable electronic gadgets, even though the Court already possesses all of the necessary equipment and facilities.